Pertenencia y compromiso: factores relevantes en la transición generacional de empresas familiares. Caso constructoras Campeche, México (2011)
The purpose of this research work was to provide a description of the sense of belonging and commitment on the part of shareholding family members in family-owned businesses specialized in the road construction industry. The design of this research work is descriptive, non-experimental and cross-sectional in nature. First, company owners were interviewed in order to identify family-owned businesses. A questionnaire was then administered to 64 managers who were also board of director members at these companies. The findings demonstrate a stronger sense of belonging than commitment to their organizations. It can be concluded that these factors impact generational transition because shareholders who are also family members are part of the board of directors at these kinds of companies.